Edukasi Kesehatan Remaja : Peningkatan Pengetahuan Remaja tentang Bahaya Rokok Elektrik - Fikria Nur Ramadani; Nina Yusnia; Nazira Auri Nurhabsyah (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
The controversy surrounding the use of electronic cigarettes (e-cigarettes) or vapes has become a new trend and is increasingly being used among teenagers. The cases of e-cigarette use are increasing year by year, while there are no clear regulations in Indonesia governing the use of e-cigarettes among teenagers. The aim of this outreach is to increase knowledge about the dangers of electronic cigarettes, thereby reducing their usage among teenagers. The educational method used was health education with a question-and-answer discussion. The respondents who participated in the educational activity were 62 people. Based on the results of the analysis test, there is a significant relationship between the knowledge of adolescents before and after the education.